How Does Digital Banking-Driven Financial Inclusion Affect Income Inequality in Türkiye? - Ahmet Usta (İktisat Politikası Araştırmaları Dergisi)
This study empirically investigates the impact financial inclusion through digital banking channels has on income inequality in Türkiye using quarterly data for the 2011:Q1-2021:Q4 period. The study uses the Gini index to measure the dependent variable of income inequality and employs two variables as proxies for digital banking. The first variable is the share of the investment volume in the total financial transaction volume made by retail customers through Internet banking. The second variable is a factor constructed based on the transaction volume per unitof main items under financial transactions. The study relies on time series approaches to test whether digital banking-driven financial inclusion has a significant impact on income inequality in Türkiye. As for the empirical evidence, the study employs the dynamic ordinary least squares method to obtain long-run coefficients, a vector autoregressive model to obtain short-run dynamics through impulse response functions with biascorrected bootstrap confidence intervals that account for the bias and skewness of the small sample, and a causality analysis. The findings show that digital financial inclusion has a widening impact on income inequality. Regarding the dynamic interactions, the Gini coefficient has been discovered to increase in response to digital banking innovations. The findings also reveal digital banking to have a forecasting ability on income inequality in Türkiye regarding the sample period.